2021
DOI: 10.2147/ijn.s325891
|View full text |Cite
|
Sign up to set email alerts
|

iRGD Peptide-Mediated Liposomal Nanoparticles with Photoacoustic/Ultrasound Dual-Modality Imaging for Precision Theranostics Against Hepatocellular Carcinoma

Abstract: Purpose Prepare a multifunctional ultrasound molecular probe, cell-penetrating peptide-modified 10-hydroxycamptothecin-loaded phase-transformation lipid nanoparticles (iRGD-ICG-10-HCPT-PFP-NPs), and to combine iRGD-ICG-10-HCPT-PFP -NPs with low-intensity focused ultrasound (LIFU) for precision theranostics against hepatocellular carcinoma (HCC). Materials and Methods The morphology of nanoparticles (NPs) and iRGD-ICG-10-HCPT-PFP-NPs was detected. In vitro, we examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The NPs with ultrasound/PA dual-modality imaging capability could penetrate deeply into the tumor and release the drug under LIFU irradiation. 113 Stearyl glycyrrhetinate (SG) is a derivative of GA. It has been demonstrated that GA and its derivatives may be used as ligands targeting the liver.…”
Section: Organic Npsmentioning
confidence: 99%
“…The NPs with ultrasound/PA dual-modality imaging capability could penetrate deeply into the tumor and release the drug under LIFU irradiation. 113 Stearyl glycyrrhetinate (SG) is a derivative of GA. It has been demonstrated that GA and its derivatives may be used as ligands targeting the liver.…”
Section: Organic Npsmentioning
confidence: 99%
“…Nanocarriers were synthesized following the previously reported thin-film hydration method and phacoemulsification method [ 38 ]. First, DPPC 5 ​mg, DSPE-PEG2000-Mal 2 ​mg, cholesterol 1 ​mg, and 20 ​μL Fe 3 O 4 were added to a round-bottom flask and dissolved in 5 ​mL trichloromethane.…”
Section: Methodsmentioning
confidence: 99%
“…The CCK-8 assay was used to detect the cytotoxicity of MNDs to Huh7 and mMNDs to Hepa1-6. The specific method was the same as the previous study [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 129 As theranostics against hepatocellular carcinoma, Li et al constructed a multifunctional molecular probe from iRGD-modified phase transformation lipid nanoparticles loaded with the chemotherapeutic agent 10-hydroxycamptothecin. 130 The NPs demonstrated their suitability for dual ultrasound/PA imaging and the ability of tumor targeting, deep penetration into the tumor, and drug release under focused low-intensity ultrasound.…”
Section: Imaging Techniquesmentioning
confidence: 96%